Probing the substrate binding modes and catalytic mechanisms of bleg-1, a promiscuous b3 metallo-β-lactamase with glyoxalase ii properties - Au, Shaw Xian; Mohd Padzil, Azyyati; Muhd Noor, Noor Dina; Matsumura, Hiroyoshi; Raja Abdul Rahman, Raja Noor Zaliha; Normi, Yahaya M. (Public Library of Science, 2023)
BLEG-1 from Bacillus lehensis G1 is an evolutionary divergent B3 metallo-β-lactamase (MBL) that exhibited both β-lactamase and glyoxalase II (GLXII) activities. Sequence, phylogeny, biochemical and structural relatedness of BLEG-1 to B3 MBL and GLXII suggested BLEG-1 might be an intermediate in the evolutionary path of B3 MBL from GLXII. The unique active site cavity of BLEG-1 that recognizes both β-lactam antibiotics and S-D-lactoylglutathione (SLG) had been postulated as the key factor for its dual activity. In this study, dynamic ensembles of BLEG-1 and its substrate complexes divulged conformational plasticity and binding modes of structurally distinct substrates to the enzyme, providing better insights into its structure-to-function relationship and enzymatic promiscuity. Our results highlight the flexible nature of the active site pocket of BLEG-1, which is governed by concerted loop motions involving loop7+α3+loop8 and loop12 around the catalytic core, thereby moulding the binding pocket and facilitate interactions of BLEG-1 with both ampicillin and SLG. The distribution of (i) predominantly hydrophobic amino acids in the N-terminal domain, and (ii) flexible amino acids with polar and/or charged side chains in both N- and C-termini provide additional advantages to BLEG-1 in confining the aromatic group of ampicillin, and polar groups of SLG, respectively. The importance of these residues for substrates binding was further confirmed by the reduction in MBL and GLXII activities upon alanine substitutions of Ile-10, Phe-57, Arg-94, Leu-95, and Arg-159. Based on molecular dynamics simulation, mutational, and biochemical data presented herein, the catalytic mechanisms of BLEG-1 toward the hydrolysis of β-lactams and SLG were proposed.